Diagnosis, prevention, and treatment of coronavirus disease: a review. Issue 2 (1st February 2022) - Sarangi, Manoj Kumar; Padhi, Sasmita; Dheeman, Shrivardhan; Karn, Santosh Kumar; Patel, L. D.; Yi, Dong Kee; Nanda, Sitansu Sekhar
ABSTRACT: Introduction: Coronavirus disease (COVID-19) was first reported in Wuhan, China, in late December 2019 and subsequently, declared a pandemic. As of 3 June 2021, 172, 493, 290 individuals have acquired COVID-19 and 3, 708, 334 patients have died worldwide, according to the World Health Organization. Areas covered: This review explores epidemiology; virology; pathogenesis; genomic variations; mode of transmission; clinical occurrence; diagnosis; and treatment with antiviral agents, antibiotics, and supportive therapies. It covers a nanotechnology-based treatment approach and emphasizes the importance of herbal and marine antiviral drugs. The review attempts to explain current advances in research, prevention, and control of COVID-19 spread through artificial intelligence and vaccine development status under cosmopolitan consideration. Expert opinion: While COVID-19 research is advancing at full capacity, the discovery of drugs or vaccines that can fight the pandemic is necessary. Human survival in such a critical situation will be possible only with the development of strong immunity by opting for exercise, yoga, and consumption of hygienic food and beverages. Therefore, education about COVID-19 lethality and its impact on livelihood is important. The pandemic has also shown positive effects on the environment, such as a significant reduction in environmental pollution and global warming and improvement in river water quality.